Prinsip-Prinsip Kesantunan Berbahasa dalam Islam - Satriah, Satriah (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
The aim of this research is to describe the principles of language politeness in Islam. This research uses literature study (library research), to obtain theoretical data regarding language politeness in Islam. The data sources used in this research are secondary, mostly using books and reputable scientific journals. The results of this research show that, in the Qur'an, the command to maintain language is symbolized by the words qaulan (spoken or spoken). Maintaining oral or spoken language is generally seen as the basis for politeness in language because the tongue is the main tool for interacting between fellow humans in various interests and situations. Guarding your tongue is the main basis for polite communication. Every human being has the responsibility to guard his tongue by speaking good words and for good purposes, the principle of politeness in Islam is shown by several terms in the Koran such as Qaulan sadidȃ: 'Qaulan Layyina, Qaulan ma'rufa.